Simulation of quinoa (Chenopodium quinoa) yield and soil salinity under salinity and water stress using the SALTMED model. Issue 18 (10th October 2020) - Peyghan, Khashayar; Golabi, Mona; Albaji, Mohammad
ABSTRACT: Due to increasing soil and water salinity in arid and semiarid regions around the world, people in these areas suffer from the lack of fresh quality water for drinking, irrigation, production of crops and livestock. This research was thus carried out in Khuzestan province, in the southwest of Iran, with a hot and dry climate, to simulate quinoa ( Chenopodium quinoa ) yield and soil salinity under salinity and water stress using the SALTMED model. To that end, the field data from a split-plot experiment with a randomized complete block design including treatments with four levels of water salinity (Karun river water, ECW 10, 20 and 30 dS/m) and three levels of irrigation (full irrigation (278 mm), regulated deficit irrigation at 75% (208 mm) and 50% (139 mm)), were used. The results showed that saline water and deficit irrigation negatively affected most investigated parameters of yield and yield components of quinoa; however, quinoa was able to grow even with ECw 20 (dS/m) under deficit irrigation at 50%. According to the results of sensitivity analysis, the irrigation water amount had the most effect on the output parameters of the SALTMED model. Once successfully calibrated and validated, the model proved to be efficient for estimating the quinoa crop yield and soil salinity under different irrigation strategies and water qualities. Besides, the coefficients of determination (R 2 ) obtained for simulating yield response of quinoa crop and soil salinity were 0.922 and 0.992, respectively. The results also showed no significant difference in model performance in simulating quinoa crop yield compared to soil salinity simulation.